2021
DOI: 10.1093/jac/dkab345
|View full text |Cite
|
Sign up to set email alerts
|

Gastric acid suppression, lifestyle factors and intestinal carriage of ESBL and carbapenemase-producing Enterobacterales: a nationwide population-based study

Abstract: Background Gastric acid-suppressive therapy has been suggested to increase the risk for intestinal carriage of MDR Enterobacterales, but there is scarce community-based evidence substantiating this risk. Objectives To investigate if acid-suppressant use is associated with a risk of intestinal carriage of ESBL and carbapenemase-producing Enterobacterales (ESBL-E) in the open population, and to assess possible modifying factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Nonetheless, a population-based prevalence study was recently conducted in the Netherlands investigating predictors of ESBL-producing Enterobacterales carriage as compared to non-carriers in the community. Consistent with our results, this study also reported that population density was not predictive of higher incidence [ 21 ]. Although a mathematical modelling study had suggested that the probability of ESBL-Ec transmission could be higher within denser households, transmission can be attenuated with good hand hygiene practices [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nonetheless, a population-based prevalence study was recently conducted in the Netherlands investigating predictors of ESBL-producing Enterobacterales carriage as compared to non-carriers in the community. Consistent with our results, this study also reported that population density was not predictive of higher incidence [ 21 ]. Although a mathematical modelling study had suggested that the probability of ESBL-Ec transmission could be higher within denser households, transmission can be attenuated with good hand hygiene practices [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Another limitation in our study is that healthcare-associated risk factors, such as community consumption of antibiotics and hospital exposure, were not accounted in the analyses. While modelling studies have predicted that reducing overall antibiotic use could reduce drastically ESBL-producing bacteria colonisation [ 30 ], other population-based studies have reported that these predictors were not significantly associated with or had limited contribution to ESBL-Ec incidence in the community [ 10 , 21 ]. These healthcare-associated risk factors may account for some of the residual spatially structured effects detected in the Brisbane city area, where accessibility to antibiotics and medical care is higher as compared to remote areas.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the risk factors for people in the community, in some studies, regular contact with children and animals, and consumption of contaminated food (e.g., meat products and aquatic food) have been identified as risk factors for acquiring MDR-Ent [99,100,105,106,[111][112][113][114]. More importantly, international travel (see below), previous hospitalization, and general health status (e.g., underlying disease, extreme age group, body mass index ≥ 25 kg/m 2 ) are significantly associated with the carriage of MDR bacteria (e.g., [67,111,115]). For instance, HIV-positive individuals are at increased risk for acquiring MDR-Ent [116].…”
Section: Community Settingmentioning
confidence: 99%
“…Details of the microbiological methods have been described elsewhere 15 and are summarised in the appendix (p 2).…”
Section: Detection Of Esbl-producing Enterobacteralesmentioning
confidence: 99%